Low-cost titanium-zirconium-based superhard self-lubricating tool coating as well as preparation method and application thereof
Patent Information
- Application Number
- CN202411277277.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
The existing tool coatings have low hardness and poor wear resistance at high temperatures, resulting in severe tool wear and increased processing resistance, which may lead to tool breakage, and may easily appear adhesion and chip accumulation when cutting stainless steel materials, resulting in heat accumulation and the blade cracked.
A low-cost titanium-zirconium-based superhard self-lubricating tool coating was designed, and by introducing elements such as Zr, Si, Al, Cr, Hf, Y, Nb into the coating structure, a dense TiO2 structure and amorphous layer were formed. Combining the composite structure of nitride and carbide, the high-temperature mechanical properties and oxidation resistance of the coating are improved, and the surface hardness and friction coefficient are optimized through ion implantation and magnetron sputtering processes.
It significantly improves the high-temperature hardness and wear resistance of the coating, reduces the friction coefficient, extends the tool service life, reduces adhesion and chip accumulation, and improves the stability and efficiency of the cutting process.
Smart Images

Figure CN119121141A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of tool coatings, and in particular to a low-cost titanium-zirconium-based superhard self-lubricating tool coating and a preparation method and application thereof. Background Art
[0002] When cutting stainless steel materials such as SUS304, SUS316, SUS301, these materials generally have high viscosity, poor thermal conductivity and work hardening, which leads to cutting heat accumulation on the tool surface and rapid cutting temperature rise, resulting in serious tool wear, poor surface roughness in the processing area, and a short service life. Especially when the tool's processing feed rate increases, the surface strength and hardness of the tool base are insufficient, and the poor lubricity are particularly obvious. Once the tool is worn, the processing resistance of the tool increases sharply, which is likely to cause the tool to break. After the tool is worn, the surface becomes rough, and the cutting edge is very likely to adhere to the processing material, resulting in built-up edge, causing heat accumulation and leading to tool edge cracking.
[0003] In the Chinese patent with application number 202310681051.4, the coating has a higher bonding strength by setting a bonding layer with good toughness and low hardness between the tool substrate and the multi-layer coating, but no pre-treatment hardness gradient design is performed, and the bonding strength needs to be improved; the hardness of the coating after high-temperature annealing is a major mechanical parameter of the thermal stability of the coating structure, and is also an important indicator of whether it can be used for a long time. The Al-based coating of this invention has excellent antioxidant properties, but the mechanical properties are insufficient at high temperatures, and it is easy to wear during the tool cutting process; in the Chinese patent with application number 201680023831.8, the hardness of the embodiment is shown as 2200HV-3200HVG, the hardness is low, and the wear resistance needs to be improved; the purpose of this invention is to improve the anti-adhesion performance during the cutting process of titanium alloys; the coating of this invention is mainly composed of Al elements, and has excellent antioxidant properties, but the mechanical properties are insufficient at high temperatures, and it is easy to wear during the tool cutting process; the embodiment shows that the coating thickness is about 3um, the coating thickness is relatively thin, and the impact resistance The impact performance needs to be improved; in the coating preparation process, the film is directly plated after Ar ion etching, and the pre-treatment hardness gradient design is not performed, and the bonding strength needs to be improved; in the Chinese patent with application number 202310559774.7, a magnetron sputtering method is used. It can be seen from the accompanying drawings of the embodiment that the bonding strength (Lc1) between the coating and the substrate is weak, and the embodiment before oxidation is less than 5N, and the crack resistance is weak; the hardness of the embodiment is only 28.8GPa, and the wear resistance needs to be improved; the coating thickness is thin, and the embodiment The thickness is only about 1um, and the impact resistance is not strong; during the coating preparation process, 3 groups of target materials are sputtered simultaneously, the process is complicated, and the repetition rate is low; in the Chinese patent with application number 202410258123.9, arc evaporation coating technology is used to prepare the coating, and the linear expansion coefficients of the insulating Al2O3 layer and the lubricating CrN layer are significantly different. The surface hardness of the prepared coating is 33-40GPa, and it is easy to peel off during service; the surface layer is a lubricating CrN layer with a friction coefficient of 0.3-0.4, and the lubrication effect is poor. Summary of the invention
[0004] The present invention designs and develops a low-cost titanium-zirconium-based superhard self-lubricating tool coating. The invention aims to solve the problems of low high-temperature hardness, weak wear resistance and difficult chip removal of existing tool coatings.
[0005] The present invention designs and develops a method for preparing a low-cost titanium-zirconium-based superhard self-lubricating tool coating. The purpose of the present invention is to obtain a low-cost titanium-zirconium-based superhard self-lubricating tool coating through coating structure design and process parameter adjustment during the preparation process.
[0006] The present invention designs and develops an application of a low-cost titanium-zirconium-based superhard self-lubricating tool coating. The purpose of the present invention is to solve the application problem of the coating in dry cutting tools.
[0007] The technical solution provided by the present invention is:
[0008] A method for preparing a low-cost titanium-zirconium-based superhard self-lubricating tool coating comprises the following steps:
[0009] Step 1: After cleaning the sample to be plated, place it in a coating furnace, evacuate the vacuum, and then perform ion implantation;
[0010] Step 2: Adjust the argon gas flow rate, maintain the vacuum state, and turn on the TiZrAlCrSiM target arc power supply to deposit the bonding layer;
[0011] Step 3: Adjust the mixed gas flow of nitrogen and argon to maintain a vacuum state and deposit the functional layer;
[0012] Step 4: turn off the nitrogen and argon gas flows, introduce acetylene gas, maintain vacuum state, deposit the lubricating layer, turn off the TiZrAlCrSiM target arc power supply, cool, and obtain the low-cost titanium zirconium-based superhard self-lubricating tool coating.
[0013] Preferably, in step 1, the cleaning process of the sample to be plated includes: immersing the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-drying the surface.
[0014] Preferably, in step 1, the vacuum is evacuated to 1.3×10 -4 Pa ion implantation was performed, and the implanted elements were Zr, Ti and N in turn, the implantation energy was 40keV~120keV, and the implantation dose was 0.5~2×10 17 ions·cm -2 ; Among them, 1×10 17 ions·cm -2 The time is 6h.
[0015] Preferably, in step 1, the Zr ion implantation parameters are: ion beam energy 120keV-80keV, adjustment once every 2 hours, implantation non-uniformity 5%, implantation dose 0.5-2×10 17 ions·cm -2 ;
[0016] The parameters of Ti ion implantation are: ion beam energy 80keV~40keV, adjusted every 2 hours, implantation non-uniformity 5%; implantation dose 0.5~2×10 17 ions·cm -2 ;as well as
[0017] The parameters of N ion implantation are: ion beam energy 120keV~80keV, adjusted every 2 hours, implantation non-uniformity 5%; implantation dose 0.5~2×10 17ions·cm -2 .
[0018] Preferably, in step 2, the coating speed is set to 2 r / min to 1 r / min, and the furnace temperature is set to 400 to 480°C and the vacuum degree is lower than 5.0×10 -3 After Pa, the bonding layer, functional layer and lubricating layer begin to be deposited in sequence; and
[0019] Adjust the argon flow rate to maintain the vacuum at 0.6-1.0 Pa, set the current to 90-120 A, and the bias voltage to -50--350 V for 10-30 min.
[0020] Preferably, in step three, the vacuum state is maintained at 2.4 to 3.6 Pa, the partial pressure ratio of nitrogen to argon is 1:2, the current is set to 90 to 120 A, the bias voltage is -50 to -100 V, and it lasts for 60 to 120 min.
[0021] Preferably, in step 4, the vacuum is maintained at 0.3-0.6 Pa, the current is set at 90-120 A, the bias voltage is -50--100 V, and the duration is 10-30 min.
[0022] Preferably, the target material is Ti a Zr b Al c Cr d Si e M f , formula M represents one or more of Hf, Y, and Nb, wherein a, b, c, d, e, and f satisfy 0.40≤a≤0.55, 0.15≤b≤0.25, 0.15≤c≤0.20, d=0.10, e=0.03, f=0.02, and a+b+c+d+e+f=1.
[0023] A low-cost titanium zirconium-based superhard self-lubricating tool coating is prepared using the method for preparing the low-cost titanium zirconium-based superhard self-lubricating tool coating, wherein the low-cost titanium zirconium-based superhard self-lubricating tool coating comprises a bonding layer, a functional layer and a lubricating layer deposited in sequence;
[0024] The chemical composition and mass percentage of the bonding layer are as follows: Ti: 40% to 55%, Zr: 15% to 25%, Al: 15% to 20%, Cr: 10%, Si: 3%, M: 2%; M represents one or more of Hf, Y, and Nb;
[0025] The chemical composition and mass percentage of the functional layer are: Ti: 20% to 27.5%, Zr: 7.5% to 12.5%, Al: 7.5% to 10%, Cr: 5%, Si: 1.5%, M: 1%, N: 50%; M represents one or more of Hf, Y, and Nb;
[0026] The chemical composition and mass percentage of the lubricating layer are: Ti: 20% to 27.5%, Zr: 7.5% to 12.5%, Al: 7.5% to 10%, Cr: 5%, Si: 1.5%, M: 1%, C: 50%; M represents one or more of Hf, Y, and Nb.
[0027] The invention discloses an application of a low-cost titanium-zirconium-based superhard self-lubricating tool coating in a dry cutting tool, and uses the low-cost titanium-zirconium-based superhard self-lubricating tool coating.
[0028] The beneficial effects of the present invention are:
[0029] 1. In the composition of the low-cost titanium-zirconium-based superhard self-lubricating tool coating provided by the present invention, the TiZr-based coating, at high temperature, the Zr element directly promotes the formation of thermodynamically stable rutile TiO2, and further leads to the formation of a dense TiO2-based structure (when Zr replaces Ti in TiO2 to form (Ti, Zr)O2), thereby increasing the high-temperature mechanical properties of the coating (high-temperature hardness and high-temperature wear resistance); the introduction of a small-radius Si element, in which the Si element mainly exists in the amorphous form of Si3N4, makes the coating gradually dense and increases the hardness of the coating; Al and Cr will generate Al2O3 and Cr2O3 protective oxide layers during the oxidation process, which can effectively prevent further diffusion of oxygen into the cemented carbide and ensure the high oxidation resistance of the coating; the addition of Hf, Y, and Nb elements can produce solid solution strengthening to improve the strength and hardness of the coating, and the prepared coating has a higher mixing entropy and tends to form a simple solid solution or an amorphous structure, which can meet the strengthening requirements of high entropy alloys;
[0030] 2. In the preparation method of low-cost titanium-zirconium-based superhard self-lubricating tool coating provided by the present invention, the energy-varying ion implantation pre-treatment forms an amorphous strengthening layer. Many studies have shown that surface ion implantation can effectively improve the surface hardness of the material, reduce the friction coefficient and wear, and does not change the surface morphology and roughness of the material. The present invention first injects large-diameter Zr ions with an injection energy of 80keV to 120keV; then injects small-diameter Ti ions with an injection energy of 40keV to 80keV; and finally injects smaller-diameter N ions with an injection energy of 80keV to 120keV; Zr During the ion and Ti implantation process, nuclear collision is the main process, while during the N ion implantation process, electron collision is the main process. The position distribution of the implanted elements can be precisely controlled by regulating the implantation energy. After ion implantation, the surface layer is composed of hard phases such as metal nitrides and nitrogen atom supersaturated solid solution, with a depth of about 50nm. The subsurface layer is mainly composed of metal nitrides. With the increase of the implantation dose, the previously isolated damage areas overlap, and finally a long-range disordered amorphous layer is formed. When subjected to external force, there is no plastic deformation such as grain boundary sliding, and it has higher strength and hardness, which can improve the support effect for the surface coating.
[0031] 3. In the preparation method of the low-cost titanium-zirconium-based superhard self-lubricating tool coating provided by the present invention, by adjusting the rotating speed of the rotating frame (1r / min-2r / min), the single layer of nano-coating with a thickness of more than 50nm-25nm is alternately deposited, which can produce a significant "superlattice" strengthening effect, improve the hardness of the coating while also inhibiting the interlayer expansion of cracks. The surface carbide lubrication layer, which is deposited on the basis of the hard functional layer, effectively adjusts the contradiction between the hardness of the coating and the friction coefficient. By changing the vacuum degree and the flow rate of the reaction gases nitrogen and acetylene, the hardness of the coating can be guaranteed while reducing its friction coefficient. The self-lubricating effect of the carbide lubricating coating during the cutting process can significantly reduce the friction coefficient between the coated tool and the workpiece, and has an excellent lubrication effect;
[0032] 4. The low-cost titanium zirconium-based superhard self-lubricating tool coating provided by the present invention is a composite structure of nitride and carbide with improved hydrophobicity. The functional layer TiZrAlCrSiMN is a multi-layer equal-thickness structure, and the lubricating layer TiZrAlCrSiMC is a single-layer structure. The composite of nitride and carbide is an innovative structure, and the surface carbide hydrophobicity is improved. Compared with the substrate, the hydrophobicity of the composite coating is improved by 27%-33%, and the surface anti-fouling ability is improved. In practical applications, it can reduce the influence of external impurities and processing aids on the surface, improve surface energy, and facilitate the realization of high hardness and high strength of the functional layer while achieving the self-lubricating characteristics of the carbide layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a schematic diagram of the structure of the low-cost titanium-zirconium-based superhard self-lubricating tool coating of the present invention;
[0034] Figure 2 This is a comparison chart of the nanohardness of the low-cost titanium-zirconium-based superhard self-lubricating tool coatings prepared in Examples 1 to 4 described in the present invention;
[0035] Figure 3 This is a comparison chart of the Vickers hardness of the low-cost titanium-zirconium-based superhard self-lubricating tool coatings prepared in Examples 1 to 4 described in the present invention;
[0036] Figure 4a This is a graph of the friction coefficient of the low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in Example 1 of the present invention;
[0037] Figure 4b This is a contact angle test diagram of the corresponding substrate of the low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in Example 1 of the present invention;
[0038] Figure 4c This is a contact angle test diagram of the low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in Example 1 of the present invention;
[0039] Figure 5a This is a graph of the friction coefficient of the low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in Example 2 of the present invention;
[0040] Figure 5b This is a contact angle test diagram of the corresponding substrate of the low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in Example 2 of the present invention;
[0041] Figure 5c This is a contact angle test diagram of the low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in Example 2 of the present invention;
[0042] Figure 6a This is a graph of the friction coefficient of the low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in Example 3 of the present invention;
[0043] Figure 6b This is a contact angle test diagram of the corresponding substrate of the low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in Example 3 of the present invention;
[0044] Figure 6c This is a contact angle test diagram of the low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in Example 3 of the present invention;
[0045] Figure 7a This is a friction coefficient diagram of a low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in Example 4 of the present invention;
[0046] Figure 7bThis is a contact angle test diagram of the corresponding substrate of the low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in Example 4 of the present invention;
[0047] Figure 7c This is a contact angle test diagram of the low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in Example 4 of the present invention;
[0048] Figure 8 It is a schematic diagram of the ion implantation equipment described in the present invention. DETAILED DESCRIPTION
[0049] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0050] like Figure 1 As shown, the present invention provides a low-cost titanium-zirconium-based superhard self-lubricating tool coating, comprising: a bonding layer 120, a functional layer 130 and a lubricating layer 140 deposited in sequence on a substrate 100, and the substrate 100 also includes a base material surface injection layer 110;
[0051] The chemical composition and mass percentage of the bonding layer 120 are as follows: Ti: 40% to 55%, Zr: 15% to 25%, Al: 15% to 20%, Cr: 10%, Si: 3%, M: 2%; M represents one or more of Hf, Y, and Nb;
[0052] The chemical composition and mass percentage of the functional layer 130 are: Ti: 20% to 27.5%, Zr: 7.5% to 12.5%, Al: 7.5% to 10%, Cr: 5%, Si: 1.5%, M: 1%, N: 50%; M represents one or more of Hf, Y, and Nb;
[0053] The chemical composition and mass percentage of the lubricating layer 140 are: Ti: 20% to 27.5%, Zr: 7.5% to 12.5%, Al: 7.5% to 10%, Cr: 5%, Si: 1.5%, M: 1%, C: 50%; M represents one or more of Hf, Y, and Nb.
[0054] like Figure 8 As shown, the present invention provides an ion implantation device, the implantation method is linear implantation, and the device is mainly composed of an ion system 210, a vacuum system 220, a collection and analysis system, a control system, a water cooling system, a power supply system, an auxiliary system, etc. The prepared sample is placed in a vacuum chamber and fixed on a target table. When the vacuum degree is higher than 1×10 -3When the pressure is above Pa, start the ion implanter. After the ion source is working, first check the working status of the ion source, and then implant the workpiece. When the set injection amount is reached, turn off the ion source and stop the injection. Compared with conventional ion implantation equipment, this ion implantation equipment can inject gas ions alone, with a maximum injection depth of 500nm from the substrate surface. The injection is carried out at room temperature (water-cooled base), and 1×10 17 ions·cm -2 The time is 6h.
[0055] The present invention provides a method for preparing a low-cost titanium-zirconium-based superhard self-lubricating tool coating, comprising the following steps:
[0056] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0057] Step 2: Ion implantation: Place the cleaned sample into the ion implantation vacuum furnace chamber and evacuate to a vacuum degree greater than 1.3×10 -4 Ion implantation was performed after Pa. The implanted elements were Zr, Ti and N, respectively, the implantation energy was 40keV to 120keV, and the implantation dose was 0.5 to 2×10 17 ions·cm -2 ;
[0058] The Zr ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 0.5~2×10 17 ions·cm -2 ;
[0059] The parameters of Ti ion implantation are: ion beam energy 80keV~40keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 0.5~2×10 17 ions·cm -2 ;
[0060] The N ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 0.5~2×10 17 ions·cm -2 ;
[0061] Step 3: After the injection is completed, take out the sample and put it into the coating furnace. Set the rotating speed of the rotating frame to 2r / min~1r / min, wait until the furnace chamber temperature reaches 400~480℃ and the vacuum degree is less than 5.0×10 -3 After Pa, the deposition of the low-cost titanium-zirconium-based superhard self-lubricating tool coating began:
[0062] Depositing the bonding layer 120: adjusting the argon flow rate to maintain the vacuum at 0.6-1.0 Pa, turning on the TiZrAlCrSiM target arc power supply to deposit the soft layer metal TiZrAlCrSiM (bonding layer 120), setting the current to 90-120A, the bias voltage to -50--350V, and continuing for 10-30min;
[0063] Depositing the functional layer 130: adjusting the flow rates of nitrogen and argon, maintaining the vacuum at 2.4-3.6 Pa (nitrogen-argon partial pressure ratio of 1:2), depositing the functional layer TiZrAlCrSiMN (functional layer 130), setting the current to 90-120 A, the bias voltage to -50--100 V, and continuing for 60-120 min; as a preferred embodiment, when depositing the functional layer, nitrogen can also be introduced separately for flow rate adjustment;
[0064] Depositing lubricating layer 140: Turn off the flow of nitrogen and argon, introduce acetylene gas, maintain the vacuum at 0.3-0.6 Pa, deposit the lubricating layer TiZrAlCrSiMC (lubricating layer 140), set the current to 90-120A, the bias voltage to -50--100V, and continue for 10-30 minutes;
[0065] Among them, the target material is Ti a Zr b Al c Cr d Si e M f , formula M represents one or more of Hf, Y, and Nb, wherein a, b, c, d, e, and f satisfy 0.40≤a≤0.55, 0.15≤b≤0.25, 0.15≤c≤0.20, d=0.10, e=0.03, f=0.02, and a+b+c+d+e+f=1;
[0066] Turn off the TiZrAlCrSiM target arc power supply;
[0067] Step 4: After coating is completed, cool to room temperature in the furnace.
[0068] In another embodiment, in step three, a lubricating layer 140 is deposited: the flow of nitrogen and argon is turned off, acetylene gas is introduced, the vacuum is maintained at 0.3-0.6 Pa, a lubricating layer TiZrAlCrSiMC (lubricating layer 140) is deposited, the current is set to 90-120 A, the bias voltage is -50--100 V, and the duration is 10-20 min.
[0069] The present invention will be further described below in conjunction with specific embodiments.
[0070] Example 1
[0071] The present invention provides a method for preparing a low-cost titanium-zirconium-based superhard self-lubricating tool coating, comprising the following steps:
[0072] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0073] Step 2: Ion implantation: Place the cleaned sample into the ion implantation vacuum furnace chamber and evacuate to a vacuum degree greater than 1.3×10 -4 Ion implantation is performed after Pa; the implanted elements are Zr, Ti and N in sequence;
[0074] The Zr ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0075] The parameters of Ti ion implantation are: ion beam energy 80keV~40keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0076] The N ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 2×10 17 ions·cm -2 ;
[0077] Step 3: After the injection is completed, take out the sample and put it into the coating furnace. Set the rotating speed of the rotating frame to 2r / min~1r / min, wait until the furnace chamber temperature reaches 400~480℃ and the vacuum degree is less than 5.0×10 -3 After Pa, the deposition of the low-cost titanium-zirconium-based superhard self-lubricating tool coating began:
[0078] Depositing the bonding layer TiZrAlCrSiM: adjusting the argon flow rate to maintain the vacuum at 0.6-1.0 Pa, turning on the TiZrAlCrSiM target arc power supply to deposit the soft layer metal TiZrAlCrSiM, setting the current to 90-120A, the bias voltage to -50--350V, and continuing for 30min;
[0079] Deposition of functional layer TiZrAlCrSiMN: adjust the flow rate of nitrogen and argon, maintain the vacuum at 2.4-3.6 Pa (nitrogen-argon partial pressure ratio is 1:2), deposit the functional layer TiZrAlCrSiMN, set the current to 90-120 A, bias voltage -50--100 V, and last for 60 min;
[0080] Depositing the lubricating layer TiZrAlCrSiMC: turn off the flow of nitrogen and argon, introduce acetylene gas, maintain the vacuum at 0.3-0.6 Pa, deposit the lubricating layer TiZrAlCrSiMC, set the current to 90-120 A, the bias voltage to -50--100 V, and continue for 25 min;
[0081] Among them, the target material is Ti 0.40 Zr 0.25 Al 0.20 Cr 0.10 Si 0.03 Y 0.02 ;
[0082] Turn off the TiZrAlCrSiM target arc power supply;
[0083] Step 4: After coating is completed, cool to room temperature in the furnace.
[0084] The low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in this embodiment includes a bonding layer TiZrAlCrSiM, a functional layer TiZrAlCrSiMN and a lubricating layer TiZrAlCrSiMC deposited in sequence;
[0085] Among them, the chemical composition and mass percentage of the bonding layer TiZrAlCrSiM are: Ti: 40%, Zr: 25%, Al: 20%, Cr: 10%, Si: 3%, Y: 2%; the chemical composition and mass percentage of the functional layer TiZrAlCrSiMN are: Ti: 20%, Zr: 12.5%, Al: 10%, Cr: 5%, Si: 1.5%, Y: 1%, N: 50%; the chemical composition and mass percentage of the lubricating layer TiZrAlCrSiMC are: Ti: 20%, Zr: 12.5%, Al: 10%, Cr: 5%, Si: 1.5%, Y: 1%, C: 50%.
[0086] Example 2
[0087] The present invention provides a method for preparing a low-cost titanium-zirconium-based superhard self-lubricating tool coating, comprising the following steps:
[0088] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0089] Step 2: Ion implantation: Place the cleaned sample into the ion implantation vacuum furnace chamber and evacuate to a vacuum degree greater than 1.3×10 -4 Ion implantation is performed after Pa; the implanted elements are Zr, Ti and N in sequence;
[0090] The Zr ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0091] The parameters of Ti ion implantation are: ion beam energy 80keV~40keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0092] The N ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 2×10 17 ions·cm -2 ;
[0093] Step 3: After the injection is completed, take out the sample and put it into the coating furnace. Set the rotating speed of the rotating frame to 2r / min~1r / min, wait until the furnace chamber temperature reaches 400~480℃ and the vacuum degree is less than 5.0×10 -3 After Pa, the deposition of the low-cost titanium-zirconium-based superhard self-lubricating tool coating began:
[0094] Depositing the bonding layer TiZrAlCrSiM: adjusting the argon flow rate to maintain the vacuum at 0.6-1.0 Pa, turning on the TiZrAlCrSiM target arc power supply to deposit the soft layer metal TiZrAlCrSiM, setting the current to 90-120A, the bias voltage to -50--350V, and continuing for 15min;
[0095] Deposition of functional layer TiZrAlCrSiMN: adjust the flow rate of nitrogen and argon, maintain the vacuum at 2.4-3.6 Pa (nitrogen-argon partial pressure ratio is 1:2), deposit the functional layer TiZrAlCrSiMN, set the current to 90-120 A, bias voltage -50--100 V, and last for 90 min;
[0096] Depositing the lubricating layer TiZrAlCrSiMC: turn off the flow of nitrogen and argon, introduce acetylene gas, maintain the vacuum at 0.3-0.6 Pa, deposit the lubricating layer TiZrAlCrSiMC, set the current to 90-120 A, the bias voltage to -50--100 V, and continue for 20 min;
[0097] Among them, the target material is Ti 0.40 Zr 0.25 Al 0.20 Cr 0.10 Si 0.03 Nb 0.02 ;
[0098] Turn off the TiZrAlCrSiM target arc power supply;
[0099] Step 4: After coating is completed, cool to room temperature in the furnace.
[0100] The low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in this embodiment includes a bonding layer TiZrAlCrSiM, a functional layer TiZrAlCrSiMN and a lubricating layer TiZrAlCrSiMC deposited in sequence;
[0101] Among them, the chemical composition and mass percentage of the bonding layer TiZrAlCrSiM are: Ti: 40%, Zr: 25%, Al: 20%, Cr: 10%, Si: 3%, Nb: 2%; the chemical composition and mass percentage of the functional layer TiZrAlCrSiMN are: Ti: 20%, Zr: 12.5%, Al: 10%, Cr: 5%, Si: 1.5%, Nb: 1%, N: 50%; the chemical composition and mass percentage of the lubricating layer TiZrAlCrSiMC are: Ti: 20%, Zr: 12.5%, Al: 10%, Cr: 5%, Si: 1.5%, Nb: 1%, C: 50%.
[0102] Example 3
[0103] The present invention provides a method for preparing a low-cost titanium-zirconium-based superhard self-lubricating tool coating, comprising the following steps:
[0104] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0105] Step 2: Ion implantation: Place the cleaned sample into the ion implantation vacuum furnace chamber and evacuate to a vacuum degree greater than 1.3×10 -4 Ion implantation is performed after Pa; the implanted elements are Zr, Ti and N in sequence;
[0106] The Zr ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0107] The parameters of Ti ion implantation are: ion beam energy 80keV~40keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0108] The N ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 2×10 17 ions·cm -2 ;
[0109] Step 3: After the injection is completed, take out the sample and put it into the coating furnace. Set the rotating speed of the rotating frame to 2r / min~1r / min, wait until the furnace chamber temperature reaches 400~480℃ and the vacuum degree is less than 5.0×10 -3 After Pa, the deposition of the low-cost titanium-zirconium-based superhard self-lubricating tool coating began:
[0110] Depositing the bonding layer TiZrAlCrSiM: adjusting the argon flow rate to maintain the vacuum at 0.6-1.0 Pa, turning on the TiZrAlCrSiM target arc power supply to deposit the soft layer metal TiZrAlCrSiM, setting the current to 90-120A, the bias voltage to -50--350V, and continuing for 25min;
[0111] Deposition of functional layer TiZrAlCrSiMN: adjust the flow rate of nitrogen and argon, maintain the vacuum at 2.4-3.6 Pa (nitrogen-argon partial pressure ratio is 1:2), deposit the functional layer TiZrAlCrSiMN, set the current to 90-120 A, bias voltage to -50--100 V, and continue for 100 min;
[0112] Depositing the lubricating layer TiZrAlCrSiMC: turn off the flow of nitrogen and argon, introduce acetylene gas, maintain the vacuum at 0.3-0.6 Pa, deposit the lubricating layer TiZrAlCrSiMC, set the current to 90-120 A, the bias voltage to -50--100 V, and continue for 20 min;
[0113] Among them, the target material is Ti 0.55 Zr 0.15 Al 0.15 Cr 0.10 Si 0.03 Y 0.02 ;
[0114] Turn off the TiZrAlCrSiM target arc power supply;
[0115] Step 4: After coating is completed, cool to room temperature in the furnace.
[0116] The low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in this embodiment includes a bonding layer TiZrAlCrSiM, a functional layer TiZrAlCrSiMN and a lubricating layer TiZrAlCrSiMC deposited in sequence;
[0117] Among them, the chemical composition and mass percentage of the bonding layer TiZrAlCrSiM are: Ti: 55%, Zr: 15%, Al: 15%, Cr: 10%, Si: 3%, Y: 2%; the chemical composition and mass percentage of the functional layer TiZrAlCrSiMN are: Ti: 27.5%, Zr: 7.5%, Al: 7.5%, Cr: 5%, Si: 1.5%, Y: 1%, N: 50%; the chemical composition and mass percentage of the lubricating layer TiZrAlCrSiMC are: Ti: 27.5%, Zr: 7.5%, Al: 7.5%, Cr: 5%, Si: 1.5%, Y: 1%, C: 50%.
[0118] Example 4
[0119] The present invention provides a method for preparing a low-cost titanium-zirconium-based superhard self-lubricating tool coating, comprising the following steps:
[0120] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0121] Step 2: Ion implantation: Place the cleaned sample into the ion implantation vacuum furnace chamber and evacuate to a vacuum degree greater than 1.3×10 -4 Ion implantation is performed after Pa; the implanted elements are Zr, Ti and N in sequence;
[0122] The Zr ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0123] The parameters of Ti ion implantation are: ion beam energy 80keV~40keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0124] The N ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 2×10 17 ions·cm -2 ;
[0125] Step 3: After the injection is completed, take out the sample and put it into the coating furnace. Set the rotating speed of the rotating frame to 2r / min~1r / min, wait until the furnace chamber temperature reaches 400~480℃ and the vacuum degree is less than 5.0×10 -3 After Pa, the deposition of the low-cost titanium-zirconium-based superhard self-lubricating tool coating began:
[0126] Depositing the bonding layer TiZrAlCrSiM: adjusting the argon flow rate to maintain the vacuum at 0.6-1.0 Pa, turning on the TiZrAlCrSiM target arc power supply to deposit the soft layer metal TiZrAlCrSiM, setting the current to 90-120A, the bias voltage to -50--350V, and continuing for 10 minutes;
[0127] Deposition of functional layer TiZrAlCrSiMN: adjust the flow rate of nitrogen and argon, maintain the vacuum at 2.4-3.6 Pa (nitrogen-argon partial pressure ratio is 1:2), deposit the functional layer TiZrAlCrSiMN, set the current to 90-120 A, bias voltage -50--100 V, and continue for 120 min;
[0128] Depositing the lubricating layer TiZrAlCrSiMC: turn off the flow of nitrogen and argon, introduce acetylene gas, maintain the vacuum at 0.3-0.6 Pa, deposit the lubricating layer TiZrAlCrSiMC, set the current to 90-120 A, the bias voltage to -50--100 V, and continue for 15 min;
[0129] Among them, the target material is Ti 0.55 Zr 0.15 Al 0.15 Cr 0.10 Si 0.03 Hf 0.02 ;
[0130] Turn off the TiZrAlCrSiM target arc power supply;
[0131] Step 4: After coating is completed, cool to room temperature in the furnace.
[0132] The low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in this embodiment includes a bonding layer TiZrAlCrSiM, a functional layer TiZrAlCrSiMN and a lubricating layer TiZrAlCrSiMC deposited in sequence;
[0133] Among them, the chemical composition and mass percentage of the bonding layer TiZrAlCrSiM are: Ti: 55%, Zr: 15%, Al: 15%, Cr: 10%, Si: 3%, Hf: 2%; the chemical composition and mass percentage of the functional layer TiZrAlCrSiMN are: Ti: 27.5%, Zr: 7.5%, Al: 7.5%, Cr: 5%, Si: 1.5%, Hf: 1%, N: 50%; the chemical composition and mass percentage of the lubricating layer TiZrAlCrSiMC are: Ti: 27.5%, Zr: 7.5%, Al: 7.5%, Cr: 5%, Si: 1.5%, Hf: 1%, C: 50%.
[0134] Comparative Example 1
[0135] The present invention provides a method for preparing a low-cost titanium-zirconium-based superhard self-lubricating tool coating, comprising the following steps:
[0136] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0137] Step 2: Ion implantation: Place the cleaned sample into the ion implantation vacuum furnace chamber and evacuate to a vacuum degree greater than 1.3×10 -4 Ion implantation is performed after Pa; the implanted elements are Zr, Ti and N in sequence;
[0138] The Zr ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0139] The parameters of Ti ion implantation are: ion beam energy 80keV~40keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0140] The N ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 2×10 17 ions·cm -2 ;
[0141] Step 3: After the injection is completed, take out the sample and put it into the coating furnace. Set the rotating speed of the rotating frame to 2r / min~1r / min, wait until the furnace chamber temperature reaches 400~480℃ and the vacuum degree is less than 5.0×10 -3 After Pa, the deposition of the low-cost titanium-zirconium-based superhard self-lubricating tool coating began:
[0142] Depositing the bonding layer TiZrAlCrSiM: adjusting the argon flow rate to maintain the vacuum at 0.6-1.0 Pa, turning on the TiZrAlCrSiM target arc power supply to deposit the soft layer metal TiZrAlCrSiM, setting the current to 90-120A, the bias voltage to -50--350V, and continuing for 15min;
[0143] Deposition of functional layer TiZrAlCrSiMN: adjust the flow rate of nitrogen and argon, maintain the vacuum at 2.4-3.6 Pa (nitrogen-argon partial pressure ratio is 1:2), deposit the functional layer TiZrAlCrSiMN, set the current to 90-120 A, bias voltage -50--100 V, and last for 90 min;
[0144] Depositing the lubricating layer TiZrAlCrSiMC: turn off the flow of nitrogen and argon, introduce acetylene gas, maintain the vacuum at 0.3-0.6 Pa, deposit the lubricating layer TiZrAlCrSiMC, set the current to 90-120 A, the bias voltage to -50--100 V, and continue for 40 min;
[0145] Among them, the target material is Ti 0.40 Zr 0.25 Al 0.20 Cr 0.10 Si 0.03 Nb 0.02 ;
[0146] Turn off the TiZrAlCrSiM target arc power supply;
[0147] Step 4: After coating is completed, cool to room temperature in the furnace.
[0148] The low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in this comparative example includes a bonding layer TiZrAlCrSiM, a functional layer TiZrAlCrSiMN and a lubricating layer TiZrAlCrSiMC deposited in sequence;
[0149] Among them, the chemical composition and mass percentage of the bonding layer TiZrAlCrSiM are: Ti: 40%, Zr: 25%, Al: 20%, Cr: 10%, Si: 3%, Nb: 2%; the chemical composition and mass percentage of the functional layer TiZrAlCrSiMN are: Ti: 20%, Zr: 12.5%, Al: 10%, Cr: 5%, Si: 1.5%, Nb: 1%, N: 50%; the chemical composition and mass percentage of the lubricating layer TiZrAlCrSiMC are: Ti: 20%, Zr: 12.5%, Al: 10%, Cr: 5%, Si: 1.5%, Nb: 1%, C: 50%.
[0150] Comparative Example 2
[0151] The present invention provides a method for preparing a low-cost titanium-zirconium-based superhard self-lubricating tool coating, comprising the following steps:
[0152] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0153] Step 2: Ion implantation: Place the cleaned sample into the ion implantation vacuum furnace chamber and evacuate to a vacuum degree greater than 1.3×10 -4 Ion implantation is performed after Pa; the implanted elements are Zr, Ti and N in sequence;
[0154] The Zr ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0155] The parameters of Ti ion implantation are: ion beam energy 80keV~40keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0156] The N ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 2×10 17 ions·cm -2 ;
[0157] Step 3: After the injection is completed, take out the sample and put it into the coating furnace. Set the rotating speed of the rotating frame to 2r / min~1r / min, wait until the furnace chamber temperature reaches 400~480℃ and the vacuum degree is less than 5.0×10 -3 After Pa, the deposition of the low-cost titanium-zirconium-based superhard self-lubricating tool coating began:
[0158] Depositing the bonding layer TiZrAlCrSiM: adjusting the argon flow rate to maintain the vacuum at 0.6-1.0 Pa, turning on the TiZrAlCrSiM target arc power supply to deposit the soft layer metal TiZrAlCrSiM, setting the current to 90-120A, the bias voltage to -50--350V, and continuing for 15min;
[0159] Deposition of functional layer TiZrAlCrSiMN: adjust the flow rate of nitrogen and argon, maintain the vacuum to 2.4-3.6 Pa (nitrogen-argon partial pressure ratio is 1:2), deposit the functional layer TiZrAlCrSiMN, set the current to 90-120 A, bias voltage -50--100 V, and last for 50 min;
[0160] Depositing the lubricating layer TiZrAlCrSiMC: turn off the flow of nitrogen and argon, introduce acetylene gas, maintain the vacuum at 0.3-0.6 Pa, deposit the lubricating layer TiZrAlCrSiMC, set the current to 90-120 A, the bias voltage to -50--100 V, and continue for 20 min;
[0161] Among them, the target material is Ti 0.40 Zr 0.25 Al 0.20 Cr 0.10 Si 0.03 Nb 0.02 ;
[0162] Turn off the TiZrAlCrSiM target arc power supply;
[0163] Step 4: After coating is completed, cool to room temperature in the furnace.
[0164] The low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in this comparative example includes a bonding layer TiZrAlCrSiM, a functional layer TiZrAlCrSiMN and a lubricating layer TiZrAlCrSiMC deposited in sequence;
[0165] Among them, the chemical composition and mass percentage of the bonding layer TiZrAlCrSiM are: Ti: 40%, Zr: 25%, Al: 20%, Cr: 10%, Si: 3%, Nb: 2%; the chemical composition and mass percentage of the functional layer TiZrAlCrSiMN are: Ti: 20%, Zr: 12.5%, Al: 10%, Cr: 5%, Si: 1.5%, Nb: 1%, N: 50%; the chemical composition and mass percentage of the lubricating layer TiZrAlCrSiMC are: Ti: 20%, Zr: 12.5%, Al: 10%, Cr: 5%, Si: 1.5%, Nb: 1%, C: 50%.
[0166] Comparative Example 3
[0167] The present invention provides a method for preparing a low-cost titanium-zirconium-based superhard self-lubricating tool coating, comprising the following steps:
[0168] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0169] Step 2: Ion implantation: Place the cleaned sample into the ion implantation vacuum furnace chamber and evacuate to a vacuum degree greater than 1.3×10 -4 Ion implantation is performed after Pa; the implanted elements are Zr, Ti and N in sequence;
[0170] The Zr ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0171] The parameters of Ti ion implantation are: ion beam energy 80keV~40keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0172] The N ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 2×10 17 ions·cm -2 ;
[0173] Step 3: After the injection is completed, take out the sample and put it into the coating furnace. Set the rotating speed of the rotating frame to 2r / min~1r / min, wait until the furnace chamber temperature reaches 400~480℃ and the vacuum degree is less than 5.0×10 -3 After Pa, the deposition of the low-cost titanium-zirconium-based superhard self-lubricating tool coating began:
[0174] Depositing the bonding layer TiZrAlCrSiM: adjusting the argon flow rate to maintain the vacuum at 0.6-1.0 Pa, turning on the TiZrAlCrSiM target arc power supply to deposit the soft layer metal TiZrAlCrSiM, setting the current to 90-120A, the bias voltage to -50--350V, and continuing for 15min;
[0175] Deposition of functional layer TiZrAlCrSiMN: adjust the flow rate of nitrogen and argon, maintain the vacuum at 2.4-3.6 Pa (nitrogen-argon partial pressure ratio is 1:2), deposit the functional layer TiZrAlCrSiMN, set the current to 90-120 A, bias voltage -50--100 V, and last for 90 min;
[0176] Depositing the lubricating layer TiZrAlCrSiMC: turn off the flow of nitrogen and argon, introduce acetylene gas, maintain the vacuum at 0.3-0.6 Pa, deposit the lubricating layer TiZrAlCrSiMC, set the current to 90-120 A, the bias voltage to -50--100 V, and continue for 20 min;
[0177] Among them, the target material is Ti 0.40 Zr 0.25 Al 0.20 Cr 0.10 Si 0.04 Y 0.01 ;
[0178] Turn off the TiZrAlCrSiM target arc power supply;
[0179] Step 4: After coating is completed, cool to room temperature in the furnace.
[0180] The low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in this comparative example includes a bonding layer TiZrAlCrSiM, a functional layer TiZrAlCrSiMN and a lubricating layer TiZrAlCrSiMC deposited in sequence;
[0181] Among them, the chemical composition and mass percentage of the bonding layer TiZrAlCrSiM are: Ti: 40%, Zr: 25%, Al: 20%, Cr: 10%, Si: 4%, Y: 1%; the chemical composition and mass percentage of the functional layer TiZrAlCrSiMN are: Ti: 20%, Zr: 12.5%, Al: 10%, Cr: 5%, Si: 2%, Y: 0.5%, N: 50%; the chemical composition and mass percentage of the lubricating layer TiZrAlCrSiMC are: Ti: 20%, Zr: 12.5%, Al: 10%, Cr: 5%, Si: 2%, Y: 0.5%, C: 50%.
[0182] Comparative Example 4
[0183] The present invention provides a method for preparing a low-cost titanium-zirconium-based superhard self-lubricating tool coating, comprising the following steps:
[0184] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0185] Step 2: Ion implantation: Place the cleaned sample into the ion implantation vacuum furnace chamber and evacuate to a vacuum degree greater than 1.3×10 -4 Ion implantation is performed after Pa; the implanted elements are Zr, Ti and N in sequence;
[0186] The Zr ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0187] The parameters of Ti ion implantation are: ion beam energy 80keV~40keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0188] The N ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 2×10 17 ions·cm -2 ;
[0189] Step 3: After the injection is completed, take out the sample and put it into the coating furnace. Set the rotating speed of the rotating frame to 2r / min~1r / min, wait until the furnace chamber temperature reaches 400~480℃ and the vacuum degree is less than 5.0×10 -3 After Pa, the deposition of the low-cost titanium-zirconium-based superhard self-lubricating tool coating began:
[0190] Depositing the bonding layer TiZrAlCrSiM: adjusting the argon flow rate to maintain the vacuum at 0.6-1.0 Pa, turning on the TiZrAlCrSiM target arc power supply to deposit the soft layer metal TiZrAlCrSiM, setting the current to 90-120A, the bias voltage to -50--350V, and continuing for 15min;
[0191] Deposition of functional layer TiZrAlCrSiMN: adjust the flow rate of nitrogen and argon, maintain the vacuum at 2.4-3.6 Pa (nitrogen-argon partial pressure ratio is 1:2), deposit the functional layer TiZrAlCrSiMN, set the current to 90-120 A, bias voltage -50--100 V, and last for 90 min;
[0192] Depositing the lubricating layer TiZrAlCrSiMC: turn off the flow of nitrogen and argon, introduce acetylene gas, maintain the vacuum at 0.3-0.6 Pa, deposit the lubricating layer TiZrAlCrSiMC, set the current to 90-120 A, the bias voltage to -50--100 V, and continue for 20 min;
[0193] Among them, the target material is Ti 0.32 Zr 0.25 Al 0.20 Cr 0.10 Si 0.03 Nb 0.10 ;
[0194] Turn off the TiZrAlCrSiM target arc power supply;
[0195] Step 4: After coating is completed, cool to room temperature in the furnace.
[0196] The low-cost titanium-zirconium-based superhard self-lubricating tool coating prepared in this comparative example includes a bonding layer TiZrAlCrSiM, a functional layer TiZrAlCrSiMN and a lubricating layer TiZrAlCrSiMC deposited in sequence;
[0197] Among them, the chemical composition and mass percentage of the bonding layer TiZrAlCrSiM are: Ti: 32%, Zr: 25%, Al: 20%, Cr: 10%, Si: 3%, Nb: 10%; the chemical composition and mass percentage of the functional layer TiZrAlCrSiMN are: Ti: 16%, Zr: 12.5%, Al: 10%, Cr: 5%, Si: 1.5%, Nb: 5%, N: 50%; the chemical composition and mass percentage of the lubricating layer TiZrAlCrSiMC are: Ti: 16%, Zr: 12.5%, Al: 10%, Cr: 5%, Si: 1.5%, Nb: 5%, C: 50%.
[0198] Test Case
[0199] In the present invention, the following performance tests were performed on Examples 1 to 5 and Comparative Examples 1 to 4:
[0200] Nanohardness test: Micro Materials Vantage nanomechanical system, based on the technical specification of JB / T12721-2016 "Solid Material In-situ Nanoindentation Scratch Tester", uses the commonly used diamond tip, 10 points are tested on each sample, and then the average value is taken. The experiment was conducted at room temperature and 500℃, with a maximum load of 50mN, a loading time of 10s, and an unloading time of 10s, to ensure that the indentation depth does not exceed 1 / 10 of the coating thickness.
[0201] Vickers hardness test: HXD-1000 Vickers microhardness tester, based on GB / T 4340.1-2009 "Metallic materials Vickers hardness test Part 1: Test method", at the 200gf force position, the loading and holding time is set to 10s, and 10 points are measured for each sample.
[0202] Friction coefficient: SiC friction pair, friction time 30min, friction radius 4mm, load 200g, speed 200r / min
[0203] As shown in Table 1, Table 2, and Table 3, the test results are as follows:
[0204] Table 1 Test results
[0205]
[0206] Table 2 Test standards and contact angle test results of Examples 1 to 4
[0207]
[0208] Table 3 Test results
[0209]
[0210]
[0211] Figure 2 The nano-hardness test results of the embodiments of the present invention are listed below. It can be seen that under the same test conditions, the maximum room temperature hardness of the coating is 42Gpa, and the maximum high temperature hardness is 35Gpa. Compared with traditional TiN, CrN, AlTiN, AlCrSiN and other coatings, the room temperature hardness is increased by 20%-60%, and the high temperature hardness is increased by 40%-90%. The titanium zirconium-based superhard tool coating prepared in the embodiment of the present application has higher room temperature and high temperature hardness, and is also resistant to high temperature wear. Figure 3The Vickers hardness test results of the embodiments of the present invention are listed as follows: It can be seen that the Vickers hardness test results are proportional to the nano hardness test results, and the maximum Vickers hardness is 3800 HV.
[0212] Figure 4a , 5a , 6a, 7a are the test results of the friction coefficient of the examples of the present invention. It can be seen that the coating prepared in the examples has a lower friction coefficient. After 30 minutes of wear, the average friction coefficient is as low as 0.19. The wear process is relatively stable and the wear resistance is excellent.
[0213] Figure 4b , 5b , 6b, 7b are the test results of the substrate contact angle of the examples of the present invention, Figure 4c , 5c , 6c, 7c are the test results of the coating contact angle of the examples of the present invention. It can be seen that the surface contact angles of the prepared coatings are improved to varying degrees, and can be increased to 33.6% at most compared with the substrate. The test results of the surface contact angle can intuitively reflect the anti-adhesion ability of the coating surface. The titanium zirconium-based superhard self-lubricating tool coating prepared in the examples can effectively inhibit the adhesive wear generated when cutting stainless steel materials such as SUS304, SUS316, and SUS301, and at the same time can make the cuttings flow out smoothly, extending the service life of the tool.
[0214] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing a low-cost titanium-zirconium-based superhard self-lubricating tool coating, characterized in that: The steps include: Step 1: After cleaning the sample to be plated, place it in a coating furnace, evacuate the vacuum, and then perform ion implantation; Step 2: Adjust the argon gas flow rate, maintain the vacuum state, and turn on the TiZrAlCrSiM target arc power supply to deposit the bonding layer; Step 3: Adjust the mixed gas flow of nitrogen and argon to maintain a vacuum state and deposit the functional layer; Step 4: turn off the nitrogen and argon gas flows, introduce acetylene gas, maintain vacuum state, deposit the lubricating layer, turn off the TiZrAlCrSiM target arc power supply, cool, and obtain the low-cost titanium zirconium-based superhard self-lubricating tool coating.
2. The method for preparing a low-cost titanium-zirconium-based superhard self-lubricating tool coating according to claim 1, characterized in that: In the step 1, the cleaning process of the sample to be plated includes: immersing the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-drying the surface.
3. The method for preparing a low-cost titanium-zirconium-based superhard self-lubricating tool coating according to claim 1 or 2, characterized in that: In step 1, the vacuum is evacuated to 1.3×10 -4 Pa ion implantation was performed, and the implanted elements were Zr, Ti and N in turn, the implantation energy was 40keV~120keV, and the implantation dose was 0.5~2×10 17 ions·cm -2 ; Among them, 1×10 17 ions·cm -2 The time is 6h.
4. The method for preparing a low-cost titanium-zirconium-based superhard self-lubricating tool coating according to claim 3, characterized in that: In step 1, the Zr ion implantation parameters are: ion beam energy 120keV-80keV, adjustment every 2 hours, implantation non-uniformity 5%, implantation dose 0.5-2×10 17 ions·cm -2 ; The parameters of Ti ion implantation are: ion beam energy 80keV~40keV, adjusted every 2 hours, implantation non-uniformity 5%; implantation dose 0.5~2×10 17 ions·cm -2 ;as well as The parameters of N ion implantation are: ion beam energy 120keV~80keV, adjusted every 2 hours, implantation non-uniformity 5%; implantation dose 0.5~2×10 17 ions·cm -2 .
5. The method for preparing a low-cost titanium-zirconium-based superhard self-lubricating tool coating according to claim 4, characterized in that: In step 2, the coating speed is set to 2 r / min to 1 r / min, and the furnace temperature is set to 400 to 480°C and the vacuum is lower than 5.0×10 -3 After Pa, the bonding layer, functional layer and lubricating layer begin to be deposited in sequence; and Adjust the argon flow rate to maintain the vacuum at 0.6-1.0 Pa, set the current to 90-120 A, and the bias voltage to -50--350 V for 10-30 min.
6. The method for preparing a low-cost titanium-zirconium-based superhard self-lubricating tool coating according to claim 4, characterized in that: In the step three, the vacuum state is maintained at 2.4 to 3.6 Pa, the partial pressure ratio of nitrogen and argon is 1:2, the current is set to 90 to 120 A, the bias voltage is -50 to -100 V, and it lasts for 60 to 120 minutes.
7. The method for preparing a low-cost titanium-zirconium-based superhard self-lubricating tool coating according to claim 6, characterized in that: In the step 4, the vacuum is maintained at 0.3-0.6 Pa, the current is set to 90-120 A, the bias voltage is -50--100 V, and the duration is 10-30 min.
8. The method for preparing a low-cost titanium-zirconium-based superhard self-lubricating tool coating according to any one of claims 1, 2, 4-7, characterized in that: The target material is Ti a Zr b Al c Cr d Si e M f , formula M represents one or more of Hf, Y, and Nb, wherein a, b, c, d, e, and f satisfy 0.40≤a≤0.55, 0.15≤b≤0.25, 0.15≤c≤0.20, d=0.10, e=0.03, f=0.02, and a+b+c+d+e+f=1.
9. A low-cost titanium-zirconium-based superhard self-lubricating tool coating, characterized in that: The low-cost titanium zirconium-based superhard self-lubricating tool coating is prepared by the method for preparing the low-cost titanium zirconium-based superhard self-lubricating tool coating according to any one of claims 1 to 8, wherein the low-cost titanium zirconium-based superhard self-lubricating tool coating comprises a bonding layer, a functional layer and a lubricating layer deposited in sequence; The chemical composition and mass percentage of the bonding layer are as follows: Ti: 40% to 55%, Zr: 15% to 25%, Al: 15% to 20%, Cr: 10%, Si: 3%, M: 2%; M represents one or more of Hf, Y, and Nb; The chemical composition and mass percentage of the functional layer are: Ti: 20% to 27.5%, Zr: 7.5% to 12.5%, Al: 7.5% to 10%, Cr: 5%, Si: 1.5%, M: 1%, N: 50%; M represents one or more of Hf, Y, and Nb; The chemical composition and mass percentage of the lubricating layer are: Ti: 20% to 27.5%, Zr: 7.5% to 12.5%, Al: 7.5% to 10%, Cr: 5%, Si: 1.5%, M: 1%, C: 50%; M represents one or more of Hf, Y, and Nb.
10. Application of a low-cost titanium-zirconium-based superhard self-lubricating tool coating in dry cutting tools, characterized in that: Use the low-cost titanium-zirconium-based superhard self-lubricating tool coating as claimed in claim 9.
Citation Information
Patent Citations
Hard coating and hard coating-covered member
CN107532280A
Anti-oxidation high-entropy nitride coating as well as preparation method and application thereof
CN116641022A
High-temperature alloy cutting coating tool and preparation method thereof
CN117026147A
Cutter and coating method thereof
CN117845180A
Cited By
Wear-resistant hard coating based on TC4 titanium alloy surface ion implantation and ion nitriding as well as preparation method and application of wear-resistant hard coating
CN121023427A
